Midiatização das migrações contemporâneas: a cobertura noticiosa do jornal nacional e sua recepção por imigrantes residentes em Porto Alegre - Fernandes, Paulo Roberto (Universidade do Vale do Rio do Sinos, 2005)
While it tries to understand the mediatization like a complex process linked at Cultural Problems Set, this research also tries to reach an investigation about how this phenomenon is structured in an specific environment, the Migrant Question, focused form two poles of the communication process: mediatical product and reception, more specific the set of news at “Jornal Nacional” news bulletin about nowadays migration and how it is received by immigrant resident in Porto Alegre. The research prime´s objective is to understand how the news set describes the migration subject, and follows to the meaning of this new´s set to immigrants. Extracts from New´s Constructivist Theory and the Scheduling Perspective grounded the comprehension of mediatical product Jornal Nacional concerned about links, about what is considered a new, about the new´s worth and about the specific terms used by journalists when talking about nowadays migration, on analyzed period. So it has developed tow methodological sets: one of them in
Keywords: competências culturais; midiatização; migrações contemporâneas; recepção; telejornalismo; cultural competences; mediatization; nowadays migrations; reception; tele-journalism; Ciências Sociais Aplicadas